Clinical significance of MRI-measured olfactory bulb height as an imaging biomarker of idiopathic Parkinson's disease. - Sohyun Park; Jungbin Lee; Jung Youn Kim; Jeong-Ho Park; Ji Eun Lee; Sang Ik Park; Younghee Yim (PLoS ONE)
Objectives This study aimed to determine whether the olfactory bulb height (OBH) measured using magnetic resonance imaging (MRI) has clinical utility as an imaging biomarker in the evaluation of patients with idiopathic Parkinson's disease (iPD) through its correlation with movement impairment. Methods This retrospective study included cognitively intact patients with suspected parkinsonism. All participants underwent T2-weighted imaging to measure OBH. Logistic regression was used to determine whether OBH was an independent risk factor for distinguishing iPD patients from disease controls, and its relation with clinical parameters related to motor impairment, including clinical laterality, modified Hoehn and Yahr (HY) stage, and Unified Parkinson's Disease Rating Scale (UPDRS) III score, was investigated. Results Based on the final clinical diagnosis, 79 patients with iPD and 16 disease controls were included. The mean OBH was significantly smaller in iPD than in disease controls (p < 0.0001). OBH was a significant independent predictor of iPD, with a cutoff of 1.52 mm. In the comparison among the ipsilateral, contralateral side of iPD with clinical laterality, and disease control group, the OBH of the disease control group was significantly larger than both the ipsilateral and contralateral sides (P < 0.05). However, there was no significant difference in OBH between the ipsilateral and contralateral sides (p > 0.05). OBH according to HY stage was significantly smaller in HY stage 2-3 groups than in the disease control group (p < 0.001). The correlation analysis between UPDRS III and OBH showed a mild negative correlation (r = -0.32, p = 0.013). Conclusions MRI-measured OBH is decreased in iPD regardless of age and sex and may be correlated with the progression of motor symptoms in the iPD.